Arc-related Alaskan type magmatism: evidence from pyroxenites associated with the Pakkanadu alkaline-ultramafic complex, Southern India - Pattnaik, Jiten; Ashutosh, Ankur; Janaarthanan, P. A.; Viljoen, Fanus; Srivastava, Rajesh K.; Ueckermann, Henriette (Frontiers in Earth Science, 2024)
Petrological and major-trace element mineral chemistry studies have been carried out on pyroxenites from the Pakkanadu Alkaline Ultramafic Complex from the southern India to understand their origin and nature of magma responsible for ultramafic magmatism in the area. Pyroxenites display cumulus texture and consist of clinopyroxenes (cpx) and amphiboles (amp) as dominant phases with a subordinate amount of apatite, biotite, ilmenite, magnetite, pyrite, sphene, and calcite. Mineral chemistry classifies cpx as augite and diopside, whereas amp falls under tremolite-actinolite and hornblende-actinolite fields. Cpx are alkaline to sub-alkaline in composition and Mg# -Al2O3 compositions suggest their crystallization under high-pressure conditions. A negative correlation between Mg# and TiO2 in cpx suggests early crystallization of magnetite and pyrite; high Mg# (76-92) suggests its link with the Alaskan-type intrusions, which may be crystallized through fractionationaccumulation process. Tectonic discrimination diagrams for cpx argue for the magmatic emplacements under an arc-tholeiitic environment in a subduction zone setting. Amp mineral chemistry (high SiO2 and low TiO2) indicate as the products of hydrothermal alteration of clinopyroxenesshows a similar nature as observed for magmatic amp of several Alaskan-type ultramafic complexes. A Low Al/Si ratio in the cpx suggests their derivation from silicaoversaturated magma, whereas low-Ti contents reflect slow cooling rate of the magma.Positive Rb, Ba and U anomalies in the multi-element patterns of the cpx probably signifying varying degrees of hydrothermal alteration in the studied samples. However, consistent Nb-Ta depletion can also be attributed to an enriched mantle source of the magma from which Formatted: Not Highlight